Validation of the Diagnostic Score for Acute Lower Abdominal Pain in Women of Reproductive Age - Jearwattanakanok, Kijja; Yamada, Sirikan; Suntornlimsiri, Watcharin; Smuthtai, Waratsuda; Patumanond, Jayanton (Emergency Medicine International, 2014)
Background. The differential diagnoses of acute appendicitis obstetrics, and gynecological conditions (OB-GYNc) or nonspecific abdominal pain in young adult females with lower abdominal pain are clinically challenging. The present study aimed to validate the recently developed clinical score for the diagnosis of acute lower abdominal pain in female of reproductive age. Method. Medical records of reproductive age women (15–50 years) who were admitted for acute lower abdominal pain were collected. Validation data were obtained from patients admitted during a different period from the development data. Result. There were 302 patients in the validation cohort. For appendicitis, the score had a sensitivity of 91.9%, a specificity of 79.0%, and a positive likelihood ratio of 4.39. The sensitivity, specificity, and positive likelihood ratio in diagnosis of OB-GYNc were 73.0%, 91.6%, and 8.73, respectively. The areas under the receiver operating curves (ROC), the positive likelihood ratios, for appendicitis and OB-GYNc in the validation data were not significantly different from the development data, implying similar performances. Conclusion. The clinical score developed for the diagnosis of acute lower abdominal pain in female of reproductive age may be applied to guide differential diagnoses in these patients.